SAFETY AND CLINICAL EFFECTIVENESS OF BILASTINE IN THE TREATMENT OF ALLERGIC RHINITIS IN CHILDREN - Bogomolov, A.Ye.; Zaikov, S.V.; Kulyk, L.G.; Plykanchuk, O.V. (World of Medicine and Biology, 2022)
The purpose of the study was to evaluate the effectiveness and safety of bilastine in relieving symptoms in patients aged 6–12 years with allergic rhinitis. In this prospective, randomized study, 50 patients aged 6 to 12 years with newly diagnosed allergic rhinitis and confirmed sensitization to allergens of household or pollen group participated; 46 completed the course of treatment within 4 weeks. Patients received bilastine orally at a dose of 10 mg daily for 4 weeks. Before starting treatment, the average level of severity of eye and nasal symptoms was assessed using the total nasal symptom score questionnaire for 5 days, with further assessment in 7, 14 and 28 days after starting bilastine intake. In general, at the endpoint of monitoring after 4 weeks, the reduction in the severity of symptoms was 49.1 %. A total of 89.1 % of patients (n=41) who received bilastine at a dose of 10 mg had no adverse reactions during the study. All adverse reactions were classified as mild, with headache being the most common, reported in 2 (4.3 %) cases.